Kielentutkimuksen menetelmiä I-IV - Luodonpää-Manni, Milla; Hamunen, Markus; Konstenius, Reetta; Miestamo, Matti; Nikanne, Urpo; Sinnemäki, Kaius (Suomalaisen Kirjallisuuden Seuran Toimituksia, 2020)
Methods in Linguistics is a collection of articles presenting a broad variety of methods and approaches in the field of linguistics. It offers structure to the spectrum of methodological possibilities and helps the reader to identify the field of application as well as the strengths and weaknesses of different methods. The book consists of an extensive introductory part and a variety of articles, each written by experts of the method in question. It discusses questions related to different kinds of data and data collection, as well as methods used for analysing data. Since the methods used in linguistics are often related to a specific linguistic current, the book offers examples from a wide range of linguistic approaches. The book is addressed to students, researchers and other readers interested in the methods used in linguistics. The general methodological and metatheoretical knowledge offered in the introduction guides the reader through the different methodological choices presented and helps the reader to select the best method to meet her needs. First, the research process is explained step-by-step from the selection of topic and data to questions related to research design, analysis and the reporting of the results. The second part of the introduction focuses on fundamental theoretical and methodological questions, such as the criteria for knowledge, the nature of scientific knowledge and the scientific method. The third part addresses more specifically the methodology of linguistics, discussing the multifaceted nature of natural language and linguistics as a discipline. The introduction also covers many current topics in science, such as research ethics, data protection and open science principles. The book can be used as self-study material by students and researchers alike, or as course material in higher education. Learning is supported by the careful definition of terms, extensive indexes and additional readings suggested for each topic.